Joint angle measurement of manipulator and error compensation based on an IMU sensor. Issue 23 (24th October 2019) - Zhang, Tianlin; Chen, Sheng; Xu, Guozheng; Wang, Chao; Tan, Caiming
Abstract : To detect the joint angle of the manipulator accurately, a measuring method based on an IMU sensor is proposed. The sensor's attitude angles and corresponding rotation matrix are obtained according to the data of three‐axis gyroscope and three‐axis accelerometer. During the installation, the sensor's Z ‐axis direction is kept along with the motor's rotation axis direction, so that the angle of the sensor rotating around its Z ‐axis, which is the rotation angle of the motor, can be calculated by comparing the rotation relationship between the sensor's initial position and the sensor's position after the motor rotating. The largest source of result error derives from the inconsistent between the sensor's Z ‐axis direction and the motor's rotation axis direction. Consequently, an installation's error compensation method is designed to correct the sensor's Z ‐axis to the motor's rotation axis by rotating the related motor. The experiments show that the method can measure the joint angle of the manipulator accurately and calibrate the installation error effectively. The measurement result errors are confined <0.25°.